Religious Conversion among Indonesian-Chinese Celebrities - Saloom, Gazi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
Religious conversion among Chinese citizens, including among artists of Chinese descent, is taking place amidst the prejudiced relationship between the Muslim natives and those of Chinese descent. Of course, this is interesting to understand. This research aims to examine the motives of religious conversion among celebrities of Indonesian-Chinese descent, especially non-Muslims to be a Muslim through Lewis Rambo's theory of Understanding Religious Conversion and its stages. This research uses qualitative methods with social media, especially YouTube, and leading and credible online news as sources of information and data. A number of individual cases representing a particular pattern are selected for analysis using strict qualitative analysis techniques. This research found 3 factors (personal, social, and Allah’s guidance) that motivated individuals of Chinese-Indonesian descent to make decisions about converting religions from non-Muslim to Muslim, namely personal, social, and guidance from Allah. In addition, this research also found that religious conversion experienced by individuals not only had an impact on individual change but also had an impact on changes in social relations in their daily lives. This study concludes that religious conversion among Chinese artists who are the subject of the study takes place through a long process, not for a moment or a short process.